Competition between strategic data intermediaries with implications for merger policy - David Bounie; Antoine Dubus; Patrick Waelbroeck (ETH Zurich, CER-ETH - Center of Economic Research, 2023)
We build a model of competition between strategic data intermediaries collecting consumer information that they sell to firms competing in a product market. Each intermediary has access to exclusive information on a group of consumers and competes with other intermediaries on a common group of consumers. Information allows firms to distinguish different segments of the consumer demand, and an equilibrium has the following properties. (i.) The largest intermediary collects the highest number of segments and sells information in the competitive market. (ii.) The incentives of the largest intermediary to collect data increase with the competitive pressure exerted by smaller intermediaries through an escape-competition effect. (iii.) Intermediaries sell information on a larger group of consumers in the competitive market than in the monopoly markets, increasing the intensity of competition among firms. (iv.) Competition reduces the incentives of intermediaries to collect data, thus increasing consumer surplus. These results have important implications for merger policy. Indeed, mergers increase the amount of data collected by intermediaries, which reduces consumer surplus due to enhanced price discrimination. This effect takes place in the market where the merging intermediaries operate, and also in other related markets through a ripple effect.
Keywords: L13; L4; L51; 330; Competition; Data intermediaries; Data collection; Selling strategies